(3MOGFb GdHjGf aj TQM cJGH GdJHjGfs - (3Ydj Hf YjSis; (3GdWjHj , TQa GdOjf GdMSjf Hf eMeO Hf YHO Gddg GdWjHj, GdWjHj,J (B743 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi habfG dEbGeI GdHQgGf Ydi eWGdH Ydei GdeYGfi hHYO adjbhd Ydi Hf YjSi NJe Gddg dg HGdMSfi Efi Ef XaQJ HcJGH GdJHjGf ddWjHi ahLOJg Hjf cJH gPG Gdaf cGdQhM ef GdCHOGf s
(3BNQgG (B:s
(3Ke LYdgeG CNhi Ce hGMOI QGVYjf KOjjgG heG EcJai HPdc Hd PcQ CfgeG JMCdagG Ydi Cf dGjJaQbG CHOkG hGddg CYde HMbjbI cd GdCehQ hGdCMhGd Je GdcJGH HMeO Gddg hMSf Jhajbg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GddZIs